2016
DOI: 10.1177/2153368715615192
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Guardianship of Foreign-Born and Native-Born Hispanic Youth and Its Effect on Violent Victimization

Abstract: First and foremost, I would like to express my gratitude to my chair, Dr. Ojmarrh Mitchell, who from the beginning, has served as a pillar and a guide in completing my thesis. During this entire process, Dr. Mitchell was very thorough in his revisions and was always available to answer my questions. He served as my mentor and shared his wisdom throughout the course of this endeavor. He allowed me to draw from my own intellectual capacity and provided the finishing touches on those ideas. For these reasons, I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…Barban & White, 2011). Our research supports earlier work conducted in the European context (Alivernini et al, 2019;Borraccino et al, 2018;Strohmeier et al, 2011), but is in contrast with previous US research showing more bullying victimization in later generations (Eggers & Mitchell, 2016;Peguero & Williams, 2013). In fact, in none of the European countries included in our study, did we find support for an 'immigrant paradox,' i.e., less bullying victimization among firstthan second-generation immigrants.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Barban & White, 2011). Our research supports earlier work conducted in the European context (Alivernini et al, 2019;Borraccino et al, 2018;Strohmeier et al, 2011), but is in contrast with previous US research showing more bullying victimization in later generations (Eggers & Mitchell, 2016;Peguero & Williams, 2013). In fact, in none of the European countries included in our study, did we find support for an 'immigrant paradox,' i.e., less bullying victimization among firstthan second-generation immigrants.…”
Section: Discussionsupporting
confidence: 80%
“…These contrasting theoretical notions are reflected in the available empirical literature. Studies conducted in the US seem to support the idea of an immigrant paradox by showing that victimization increased with immigrant generation, which was explained by an increase in deviant behavior and by a decrease in neighborhood safety with immigrant generation (Eggers & Mitchell, 2016;Peguero & Williams, 2013). In Europe, however, the 'immigrant paradox' has not received much support (Dimitrova, Chasiotis, & van de Vijver, 2016;Stevens et al, 2015).…”
Section: Immigrant Generation Age and The Immigrationbullying Victimi...mentioning
confidence: 99%
See 1 more Smart Citation
“…We did not control for immigration status because we found it was not significantly related to violent victimization in our sample and our data set had a small percentage (12.2 %) of foreign-born individuals. Yet, studies generally show that immigrant status is a significant predictor of victimization, with Hispanic foreign-born youth being less likely to experience victimization than their native-born counterparts (Eggers & Jennings, 2014; Eggers & Mitchell, 2015). Second- and third-generation immigrant adolescents also have a greater risk of victimization compared to first-generation adolescents (Gibson & Ventura Miller, 2010; Koo, Peguero, & Shekarkhar, 2012; Peguero, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has focused on how acculturation experiences influence victimization with immigrants becoming more accultured over time as well as how such experiences increase their offending, particularly through weakened family bonds and cultural values, in turn impacting victimization ( Sommers et al, 1994 ). Alternatively, some have suggested that immigrants are less likely to be victimized because their lifestyles and routine activities decrease risk factors ( Eggers and Mitchell, 2016 ).…”
Section: Introductionmentioning
confidence: 99%